Corporate governance, board-shareholder relationship and firm performance: Evidence from financial institutions in China - Zhao, Zixuan (2020)
The extant literature exhibits extensive but inconclusive empirical results related to the effectiveness of corporate governance and the influence of board-shareholder relationship on firm-level performance, partially owing to the neglect of industry differences and firm size effect. To offer incremental insight, this paper filled the gap by forming a fixed effect model, with a concentrated data set of 107 publicly listed A-share financial institutions in China for 10 years from 2009 to 2018, to further examine in detail whether ownership concentration, shareholder affiliation and board independence would affect the performance of firms in various sizes. This study finds that, ownership concentration and shareholder affiliation exert a negative impact on performance, which bears out the Stewardship Theory that board is trustworthy and should be given more autonomy. However, the influence of shareholder affiliation on firm performance becomes surprisingly positive as firm size goes up, which suggests that closely-connected large shareholders are more effective in regulating board behaviors in large corporations. Besides, this study also finds that board independence can stimulate firm-level performance and development, which is generally agreed by the agency theorists. Apart from providing additional evidence to examine governance theories, this paper provides practical suggestions that decision makers of Chinese financial institutions should make efforts in choosing a proper managerial structure concerning the firm size, and policymakers should deepen the financial reform regarding ownership structure and board features to facilitate the development of finance industry in China.